2021
DOI: 10.1002/nau.24735
|View full text |Cite
|
Sign up to set email alerts
|

Initial experience using a novel nerve stimulator for the management of pudendal neuralgia

Abstract: In patients with pudendal neuralgia, prior studies have shown efficacy in chronic stimulation with Interstim® (Medtronic, Inc.). This feasibility study reports on the initial experience of using a wireless system to power an implanted lead at the pudendal nerve, StimWave®, to treat pudendal neuralgia.Methods: Retrospective chart review identified patients with a lead placed at the pudendal nerve for neuralgia and powered wirelessly. Clinical outcomes were assessed at Postoperative visits and phone calls. Admin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Although most case series report the results with the percutaneous implantation of tined leads, there are also descriptions of open and laparoscopic lead placement, 30 , 31 and with implantable devices. 32 Little evidence supports the management of BPS/IC with pudendal-only neuromodulation; thus, a review of chronic pelvic-perineal pain syndromes was undergone.…”
Section: Pudendal Nerve Stimulationmentioning
confidence: 99%
See 3 more Smart Citations
“…Although most case series report the results with the percutaneous implantation of tined leads, there are also descriptions of open and laparoscopic lead placement, 30 , 31 and with implantable devices. 32 Little evidence supports the management of BPS/IC with pudendal-only neuromodulation; thus, a review of chronic pelvic-perineal pain syndromes was undergone.…”
Section: Pudendal Nerve Stimulationmentioning
confidence: 99%
“…Recently, the group by Hoang Roberts et al 32 reported the effectiveness of Stimwave ® Freedom Stimulators™ (Stimwave, Pompano Beach, FL, USA) in the management of pudendal neuralgia.…”
Section: Pudendal Nerve Stimulationmentioning
confidence: 99%
See 2 more Smart Citations
“…We hypothesized that a similar spinal reflex exists for genital vasocongestion. Both pudendal and tibial nerve stimulation have the potential to improve sexual function and have specific translational advantages, including the ease of access and existing clinical use for pelvic dysfunctions 18,19,26,30 , however a greater understanding of the underlying mechanisms and neural circuitry is needed.…”
Section: Introductionmentioning
confidence: 99%